2019
DOI: 10.25273/florea.v6i2.5261
|View full text |Cite
|
Sign up to set email alerts
|

Status Mutu Air Sungai Cikaniki Kabupaten Bogor Berdasarkan Indeks Pencemaran Dan Keanekaragaman Makrofauna

Abstract: <p>Sungai Cikaniki merupakan salah satu sungai yang berhulu di Taman Nasional Gunung Halimun Salak (TNGHS) terletak di Kabupaten Bogor dipilih sebagai lokasi penelitian dikarenakan sepanjang aliran sungai Cikaniki mendapat masukkan senyawa yang berasal dari pemukiman maupun industri yang menggunakan sianida dan merkuri untuk ekstraksi bijih emas. Penelitian dilaksanakan selama bulan Maret – Juni 2019. Tujuan dari penelitian ini adalah untuk 1) Menganalisis kondisi sungai Cikaniki berdasarkan bioindikator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…There has been no research related to the content of heavy metals in water, sediment, and fish in the Cikanikiriver. The study results Azizah & Anen (2019), show that Cikaniki River watershed is polluted with light pollution levels. In 2004, Syawal &Yustiawati found that mercury (Hg) in the water had an average concentration of 35 times above the maximum limit set for Class III with a range of 0.0023 -0.1743 mg / L), up to 2019 not yet.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…There has been no research related to the content of heavy metals in water, sediment, and fish in the Cikanikiriver. The study results Azizah & Anen (2019), show that Cikaniki River watershed is polluted with light pollution levels. In 2004, Syawal &Yustiawati found that mercury (Hg) in the water had an average concentration of 35 times above the maximum limit set for Class III with a range of 0.0023 -0.1743 mg / L), up to 2019 not yet.…”
Section: Introductionmentioning
confidence: 85%
“…The levels will continue to increase if the waters continue to be polluted. Even though the Cikaniki River is categorized as lightly contaminated, its status maygrow if there is still pollution (Azizah & Anen, 2019). Under anoxic conditions, microbial activity can form arsenic in methylate, solid, and enter the atmosphere (Istarani & Pandebesie, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%